Early tolerance and late persistence as alternative drug responses in cancer - Simona Punzi; Davide Cittaro; Guido Gatti; Gemma Crupi; Oronza A. Botrugno; Antonino Alex Cartalemi; Alon Gutfreund; Caterina Oneto; Valentina Giansanti; Chiara Battistini; Giovanni Santacatterina; Lucrezia Patruno; et al. (Nature Communications)
Abstract Bacteria withstand antibiotic treatment through three alternative mechanisms: resistance, persistence or tolerance. While resistance and persistence have been described, whether drug-induced tolerance exists in cancer cells remains largely unknown. Here, we show that human cancer cells elicit a tolerant response when exposed to commonly used chemotherapy regimens, propelled by the pervasive activation of autophagy, leading to the comprehensive activation of DNA damage repair pathways. After prolonged drug exposure, such tolerant responses morph into persistence, whereby the increased DNA damage repair is entirely reversed. The central regulator of mitophagy PINK1 drives this reduction in DNA repair via the cytoplasmic relocalization of the cell identity master HNF4A, thus hampering HNF4A transcriptional activation of DNA repair genes. We conclude that exposing cancer cells to relevant standard-of-care antitumour therapies induces a pervasive drug-induced tolerant response that might be broadly exploited to increase the impact of first-line, adjuvant treatments and debulking in advanced cancers.